Identifying the Optimal Age to learn Water Polo Tactics according to Expert Opinion: Insights through Dimensionality Reduction Analysis - Goran Jelaska; Mladen Hraste; Cain C. T. Clark (OVS LLC, 2024)
Background. It is of great importance that the training process of youth water polo players be tailored to didactic principles and developmental characteristics. However, despite this importance, there is a dearth of pertinent studies. Objectives. The study aimed to determine and explain the appropriate age for beginning of learning tactical elements in water polo, as stated by experts' coaches' opinion in this sport. Materials and methods. Accordingly, 27 expert water polo coaches completed a novel questionnaire, specifically designed for this study. Results. Test-retest reliability indicated satisfactory scores (r ranged from 0.85 to 1.00 with p<0.05 for all variables). The results of the exploratory factor analysis using the Guttman-Kaiser criterion for selecting the number of factors and the Varimax raw rotation revealed the presence of six underlying factors in real-life contexts: (1) individual and group activities with a numerical advantage/disadvantage; (2) dynamic-complex collective defensive activities with an equal number of players; (3) intensive defensive activities with an equal number of players, static defensive activities with a numerical handicap and collective offensive activities with a numerical advantage; (4) static-vertical attacking activities with a numerical advantage, attacking activities with an equal number of players and dynamic defensive activities with a numerical handicap; (5) static-vertical defensive activities with an equal number of players; (6) extremely rare offensive activities which explain 19%, 16%, 17%, 11%, 11%, 6% of the manifest space variability, respectively. Conclusions. The present findings highlight novel insight into experts' opinions regarding the learning of complex water polo movements, and offer essential guidance for key stakeholders pertaining to optimizing the training processes and curricula for all youth water polo players.